Gastrointestinal stromal tumor of the small intestine of high malignant potential - Mladenović, Aleksandar M; Jovančević, Miljan; Milošević, Zoran (PONS - medicinski časopis, 2022)
Gastrointestinal stromal tumors (GIST) are defined as mesenchymal tumors of the gastrointestinal tract expressing proto-oncogene protein CD 117. GIST is a rare tumor of the small bowel, which can be difficult to diagnose and has a varied clinical outcomes . Prognosis is dependent on tumor size and mitotic count.    Radical surgical excision (R0) is the treatment of choice for resectable and non-metastatic disease. Imatinib is a first-line therapy for metastatic, unresectable or recurrent disease.    In this case report, we describe large GIST of the small bowel with high malignant potential. Eight years after the operation, the patient is in good general condition with no signs of recurrence of the disease.
Keywords: gastrointestinal stromal tumor; small bowel; c-kit proto-oncogen; surgery